PEMANFAATAN BUKU TEKS SEJARAH OLEH GURU - Al-Fajar Bima Sakti; Iis Husnul Hotimah (Jambura History and Culture Journal, 2023)
This paper provides an explanation of how the use of history textbooks by history teachers or teachers. The use of textbooks needs to be highlighted because textbooks not only function as a source of students learning but also a guide in learning activities used by teachers. Textbooks must be adapted to the needs of students and teachers so that there needs to be a suitability for use for teachers. The research method used in this study is descriptive qualitative and the data collectiontechnique used is a literature study data obtained from previous reading and research sources. In essence, textbooks have a greatcontribution to the learning of history. Textbooks as a source of learning history in schools can add insight to students so that what previously did not know becomes known. In addition, students can also explore the values in the textbook such as heroic values, nationalism values and patriotism values